Assessment of Noise Pollution and its Impact on Human Health in Hilla City - Haydder Radhi Kadhim (Journal of Global Pharma Technology, 2016)
Noise pollution is type of air pollution, it is unwanted sounds that reduce quality of person life via effect on normal activity like. It can disturb sleep, cause cardiovascular and psychophysiological effects, Material and method level of noise measured in five types of regions in hilla city during each season of year in two reading (morning and evening) with outside and inside building, then comparative the results with international and local level of sounds, in addition to estimate effect it on human healthy. This work is down by using a precision sound level meter digital instrument as noise meter. Result this study showed that some selected regions of hilla city were over normal level of sounds which make this regions suffered of noise pollution Conclusion this noise may be pollution lead to effects on physiological and psychological state of human.